Developing evidence indicators for evaluating K12 EdTech: towards a consensus on educational impact - Natalia Kucirkova; Olav Schewe; Janine Campbell; Anna Lindroos Cermakova; Nicola Pitchford (Humanities & Social Sciences Communications)
Abstract Drawing upon a synthesis of literature and cross-sectoral consultations, we present the impact dimensions and three-level tiered indicators for developing a multidimensional approach to evaluating the evidence of impact of educational technology (EdTech). We build on the “5Es” impact framework — efficacy, effectiveness, ethics, equity, and environment — by operationalising it through fifteen impact indicators identified through an extensive literature review and a participatory Delphi study involving consultations with representatives of the EdTech industry and investment across two rounds. The proposed indicators serve as impact metrics to assist policymakers, educators, and EdTech developers in comprehensively assessing the impact of EdTech solutions. Together with their relevant measurement criteria and specific technological attributes, the impact indicators fill the gap of a comprehensive multidimensional guide for international standardisation and certification efforts in EdTech quality.